The Effectiveness of a Program Based on Interactive Theater in Developing Some Behavioral Etiquette in Early Childhood - Al-Zahrani, Amjad Ahmed (Journal of Educational and Psychological Sciences, 2023)
The study aimed at identifying the effectiveness of a program based on interactive theater in developing some behavioral etiquette, also it aimed at revealed degree of continuity of the effectiveness of the program based on the interactive theater in developing some behavioral etiquette in childhood, The study relied on the semi-experimental approach with two groups: the experimental and the control. Study sample consisted of (60) children, who were divided equally into two groups, with (30) experimental group and (30) control group. Researcher used the behavioral etiquette scale, the program based on the interactive theater, and the Stanford-Binet Test of intelligence (standardized by Lewis Malika’s, 1998). The results of the study revealed the presence of a statistically significant effectiveness of the program based on the interactive theater in developing some behavioral etiquette, The results also revealed the continuity of the effectiveness of the program based on the interactive theater in developing some behavioral etiquette in the early childhood after one month the end of it application, The results were discussed and interpreted in the light of the theoretical framework and previous studies, and The study recommended some recommendations, including the necessity of activating the interactive theater in the educational process, especially the early childhood stage. Because of its positive impact on emotional and cognitive in improving the performance of children in general.